A CROSS SECTIONAL STUDY OF SUBSTANCE ABUSE AMONG UNDERGRADUATE MEDICAL STUDENTS IN A GOVERNMENT MEDICAL COLLEGE AND HOSPITAL OF NORTH BENGAL REGION (Journal of Forensic Medicine & Toxicology, 2025)
Background: Medical students have always been considered flag bearers of a noble profession, expected to treat and heal thousands of patients in the future. But when such medical students abuse substances, it poses a grave risk not only to themselves but also to their fellow colleagues and the patients. Objectives: The study was aimed at knowing the prevalence and pattern of substance abuse along with some socioeconomic factors that may be associated with substance abuse among undergraduate medical students of MJNMCH, Coochbehar, West Bengal. Methods: This cross-sectional study was conducted from February to April 2024 at MJNMCH, Coochbehar. A semi-structured, pre-tested anonymous questionnaire was prepared and distributed among the students after assuring them of confidentiality about their identity. All students were invited to participate in the study. After the exclusion of the unwilling students and incompletely filled-up questionnaires, 160 filled-up questionnaires were eligible for analysis. Results: Out of a total of 160 students, only 43 medical students used various types of substances. The proportion of substance abuse was higher among males than females. 53.49% of substance abusers were in the third year of the MBBS course. 97.67% were hostelers, 74.42% come from nuclear families, 25.58% have a history of substance abuse in their family, and 60.47% of substance abusers were from urban areas. Tobacco (60.47%) was the substance most abused. 55.81% initiated substance use after coming to medical college. 79.07% did not feel any unwanted effects, while 13 had made some attempts to quit the substances. Conclusion: The insights procured from this study will help in better understanding the mindset of the students, besides looking for avenues to curb this menace through targeted reforms like health education and student counselling.
Keywords: Substance Abuse; Medical students; Medical College; Tobacco; Drug Dependence